Seroepidemiological survey of the human immunodeficiency Virus, type 2. - Pedro, Marília L (2004)
To perform a seroepidemiological study and identify associated factors in a population infected by Human Immunodeficiency Virus, type 2 (HIV-2). A total of 2202 individuals were tested to determine the seroprevalence of this virus.A nine-years retrospective study was performed in 211 HIV-2 seropositives screened by ELISA and confirmed by Western Blot analysis. Eighty-two individuals were analised by synthetic peptides and 15 had an antibody pattern of double reactivity to HIV-1 and HIV-2.The mean age of the HIV-2 - infected individuals was 37.44+/-14.83 years (men 38,34+/-17,18 years; women 36,77+/-12,89 years). There were 23.7% infection cases (95% CI, 18.1-30.0) in the age group 40-49 years. The infection was higher in females 57.8% (95% CI, 50.8-64.6) than in males 42.2% (95% CI, 35.4-49.2). HIV-2 infection in Blacks was 61.6 % (95% CI, 54.7-68.2). In respects to their geographical origin, the Portuguese represented 51.7% (95% CI, 44.7-58.6) followed by Guinean (Bissau) with 26.5% (95% CI, 20.7-33.0). The main mode of transmission of HIV-2 infection appears to be heterosexual transmission with 59.3% (95% CI, 47.8-70.1). Most of the evaluated individuals 54.3% (95% CI, 46.6-61.9) were classified as CDC stage II. HIV-2 seroprevalence was 1%.In considering the comparative data on the two periods of 4.5 years each, an increase of the infection in Caucasians from 32.4% to 43.4% was seen as well as a reduction in Blacks from 67.6% to 55.7%. An increase in asymptomatic persons and a reduction in the CDC stage IV/C1 was also observed. This study emphasis the need to continue efforts to decrease transmission of HIV-2 that should be directed toward epidemic and endemic regions and education about the risks of sexual transmission and how to decrease transmission by this route.